2015
DOI: 10.4172/2167-7182.1000227
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Patients with Non-ST-Elevation Acute Coronary Syndrome: A Proposal to Adapt Decision Making

Abstract: The guidelines recommend invasive treatment (coronary angiography) in elderly patients with non-ST-elevation acute coronary syndrome (NSTE-ACS) with a moderate and high risk of re-infarction or death. The invasive approach has been found to be more effective in older and higher risk patients. The aim of this study was twofold: first, to determine whether the recommendations of current guidelines are followed for elderly patients with NSTE-ACS in our hospital; and second, to reach agreement among professionals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…Recommendations based on randomized trials and observational studies that have found strong evidence that invasive treatment is more beneficial in elderly patients with NSTE-ACS than younger subjects, even considering the increased risk of bleeding in the elderly. Nonetheless, our data (3) and in other studies of neighbouring countries (4,5) show a tendency to perform invasive treatment of NSTE-ACS in patients with a lower risk and a younger age, depriving many patients of invasive treatment solely because of their age without any associated functional or cognitive disorders to warrant this.…”
Section: Dear Editorsupporting
confidence: 47%
“…Recommendations based on randomized trials and observational studies that have found strong evidence that invasive treatment is more beneficial in elderly patients with NSTE-ACS than younger subjects, even considering the increased risk of bleeding in the elderly. Nonetheless, our data (3) and in other studies of neighbouring countries (4,5) show a tendency to perform invasive treatment of NSTE-ACS in patients with a lower risk and a younger age, depriving many patients of invasive treatment solely because of their age without any associated functional or cognitive disorders to warrant this.…”
Section: Dear Editorsupporting
confidence: 47%